Food Security Level of Trawl Net Fishermen Households in Tapanuli Tengah Regency, Sumatera Utara - Tirta Anugerah; Juliana P Siburian; Yoga Rasihen; Siti Mariyani; Muhammad Latiful Khobir; Husnul Yaqin Harahap; Shofian Nanda Adiprayoga (Universitas Teuku Umar, 2026)
This research is motivated by the vulnerability of small-scale fishing households to food security, particularly amid their dependence on prohibited fishing gear such as trawl nets. Despite regulations prohibiting the use of such fishing gear, many fishermen still rely on it as their primary source of livelihood due to limited alternatives and minimal policy support. This study aims to identify the level of food security of fishing households using trawl nets and analyze the structure of their food and non-food expenditures. This research was conducted using a quantitative approach, and data was collected through a survey method using a questionnaire to predetermined respondents. The results show that 70% of fishing households are classified as food insecure, while only 30% are classified as food secure. Food insecure households have higher total expenditures, but a larger proportion is allocated to non-productive consumption such as cigarettes. Conversely, food secure households tend to prioritize spending on education and other long-term needs. These findings confirm that food security is not solely determined by income, but rather by how households manage and prioritize expenditures. Policies that support the transfer of fishing gear and improve financial and nutritional literacy are urgently needed to improve fishers' food security sustainably